JIE HUA XIAN FO (PRESENTING THE BUDDHA WITH BORROWED FLOWERS): Reciprocity and Exchange among Chinese Seniors in Vancouver's Downtown Eastside. - BING YAN (BC Studies)
This document provides a list of references and interview questions for a research project on Chinese seniors in Vancouver's Downtown Eastside. The references cover topics such as transnationalism, social protection, aging, and migration, while the interview questions focus on the experiences and relationships of Chinese seniors in the community. The questions aim to understand their reasons for living in the Downtown Eastside, their social networks, experiences of racism, and access to resources like food banks.